2021
DOI: 10.3892/etm.2021.10062
|View full text |Cite
|
Sign up to set email alerts
|

miR‑1184 regulates inflammatory responses and cell apoptosis by targeting TRADD in an LPS‑induced cell model of sepsis

Abstract: MicroRNAs (miRs) have been reported to be potential clinical biomarkers for sepsis. miR-1184 is a multifunctional microRNA that exerts roles in the development of various diseases. However, the role of miR-1184 in children with sepsis remain unknown. In the present study, THP-1 cells were stimulated with 1 µg/ml lipopolysaccharide (LPS) for 24 h to establish an in vitro sepsis model. Reverse transcription-quantitative PCR was used to evaluate the expression of miR-1184 in clinical specimens, and of IL-6, TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Wang and Han (30) showed that miR-1184 was decreased in the serum of neonatal sepsis, and overexpression of miR-1184 targetedly suppressed IL-6 level to inhibit LPS-stimulated inflammatory reaction in monocytes. Besides, miR-1184 exerted anti-inflammatory effects on LPS-induced in vitro sepsis cell model by suppressing TNF-R1-associated death domain protein (TRADD) expression (31). Consistent with these findings, we also found a decrease of miR-1184 level in sepsis patients and LPS-induced MRC-5 cells, and miR-1184 re-expression showed anti-apoptotic and anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and Han (30) showed that miR-1184 was decreased in the serum of neonatal sepsis, and overexpression of miR-1184 targetedly suppressed IL-6 level to inhibit LPS-stimulated inflammatory reaction in monocytes. Besides, miR-1184 exerted anti-inflammatory effects on LPS-induced in vitro sepsis cell model by suppressing TNF-R1-associated death domain protein (TRADD) expression (31). Consistent with these findings, we also found a decrease of miR-1184 level in sepsis patients and LPS-induced MRC-5 cells, and miR-1184 re-expression showed anti-apoptotic and anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 99%
“…Once more, hsa-mir-449a inhibits cancer cell proliferation and promotes apoptosis which upturns the sensitivity to the chemotherapeutic drug resistance, so it has been considered as a therapeutic goal to alleviate chemotherapeutic drug resistance in cancer that will upsurge the effectiveness of chemotherapy [ 119 ]. hsa-mir-1184 has deregulated flow in the blood of children affected with Sepsis (Sepsis is a presumably harmful disease that happens when the body's immune system attacks its own tissues in response to an infection), along with that it can be an valuable recipient for the treatment of children with sepsis since it smears prohibited effects on inflammatory responses and apoptosis through assaulting TRADD (Tumor necrosis factor receptor type 1-associated DEATH domain protein) [ 120 ]. As well as hsa-mir-1976 has been termed as a non-invasive diagnostic object and therapeutic focus for sick sinus syndrome that is accompanying shortness of breath with opportunities to come across standpoints for mutually noticeable pathogenesis [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the experiments, cells in the logarithmic growth phase were utilized. THP-1 cells were treated with 1-µg/mL LPS for 24 h. 16 Following LPS treatment. A PSTPIP2 overexpression plasmid/vector was transfected into THP-1 cells using lipofectamine 3000 (Invitrogen, CA, USA).…”
Section: Thp-1 Cell Culture and Transfectionmentioning
confidence: 99%